2024
DOI: 10.1001/jamanetworkopen.2024.3362
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Use in Late Preterm and Full-Term Newborns

Johan Gyllensvärd,
Marie Studahl,
Lars Gustavsson
et al.

Abstract: ImportanceAntibiotic treatment saves lives in newborns with early-onset sepsis (EOS), but unwarranted antibiotic use is associated with resistant bacteria and adverse outcomes later in life. Surveillance is needed to optimize treatment strategies.ObjectiveTo describe antibiotic use in association with the incidence and mortality from EOS among late-preterm and full-term newborns.Design, Setting, and ParticipantsThe Sweden Neonatal Antibiotic Use study was a nationwide observational study that included all late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
(131 reference statements)
1
1
0
Order By: Relevance
“…The observed incidence of 0.9 culture-proven EOS cases per 1000 live births in the regional hospital population in our study falls within the range of reported EOS incidences among late preterm and term neonates in other high-income countries, varying between 0.13 and 1.45 per 1000 live births [ 20 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Predominant pathogens identified were Streptococcus agalactiae , Escherichia coli and Staphylococcus aureus , similar to the pathogen distribution in other Western countries [ 19 , 28 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The observed incidence of 0.9 culture-proven EOS cases per 1000 live births in the regional hospital population in our study falls within the range of reported EOS incidences among late preterm and term neonates in other high-income countries, varying between 0.13 and 1.45 per 1000 live births [ 20 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Predominant pathogens identified were Streptococcus agalactiae , Escherichia coli and Staphylococcus aureus , similar to the pathogen distribution in other Western countries [ 19 , 28 ].…”
Section: Discussionsupporting
confidence: 81%
“…In our study, we found that 50.5% of neonates were still receiving antibiotics after 48 h. Recent studies in The Netherlands showed that despite negative blood cultures, antibiotic treatment was continued for more than 72 h in 31.5% and 35.9% of neonates [ 22 , 29 ]. Other studies have reported median treatment durations of 3–7 days in neonates without culture-proven EOS [ 19 , 30 , 31 ]. Despite differing study objectives, the common finding is a disproportionately high number of neonates receiving antibiotics after the blood culture remains negative.…”
Section: Discussionmentioning
confidence: 99%